USE OF MODERN MARKETING RESEARCH IN THE CONTEXT OF MARKET DEVELOPMENT - Ismoilov Ravshanjon Bakhriddinovich; Mullabayev Baxtiyarjon Bulturbayevich; Mahmudova Nilufar Gulomjanovna; Usmonov Rustamjon Karimjanovich; Bakhriddinov Jahongir Ravshanjon ogli (International Engineering Journal For Research & Development, 2020)
Marketing research helps to link the marketing strategy with the factors of the marketing environment and the interests of interest groups. With their help, the management of the company receives the information he needs, which partially eliminates the uncertainty in business development.